(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
هدف هذا البحث إلى تقييم التلوث الناتج عن معمل أسمنت طرطوس من بعض العناصر الثقيلة من خلال استخدام قلف أشجار الزيتون والشيبيات كدلائل حيوية. تم اختيار أشجار الزيتون على اعتبار إنها النوع النباتي السائد في منطقة الدراسة. جمعت عينات قلف أشجار الزيتون والشيبيات المتواجدة عليها من عدة قرى محيطة بالمعمل وعلى مسافات مختلفة (1-2-3-4-5-6-7) كم من مركز المعمل في المنطقة الشرقية والشمالية الشرقية من المعمل (حيث الرياح السائدة في المنطقة غربية وجنوبية غربية). أظهرت النتائج بأن تركيز العناصر الثقيلة الموجودة في قلف أشجار الزيتون والشيبيات مقدرة بـ ppm أخذت نفس المنحى بغض النظر عن الاختلاف في التركيز بينهم وكانت على النحو التالي: حديد < منغنيز < نحاس< رصاص، مع ملاحظة التركيز العالي لعنصر الحديد في قلف أشجار الزيتون مقارنة بالشيبيات أما بقية العناصر كانت متماثلة إحصائياً. كما أظهرت النتائج وجود علاقة ارتباط معنوية بين تراكيز عنصر المنغنيز في كل من القلف والشيبيات، ووجود علاقة ارتباط سلبية بين تركيز المنغنيز عند كل من الشيبيات والقلف والمسافة. وفيما يخص الارتفاع عن سطح البحر بينت النتائج وجود علاقة ارتباط سالبة ومعنوية مع كل من الحديد والمنغنيز والرصاص في الشيبيات. This research was aimed to assess the pollution from Tartous Cement Factory of some heavy metal by using of the bark of olive trees and Lichens as Bio-indicators. The olive trees was chosen as that predominant vegetation type in the study area. Bark samples of olive trees and the lichens were collected from several villages surrounding the Cement Factory at different distances (1-2-3-4-5-6-7) km from the center of the Cement Factory in the eastern and north-eastern region of the Cement plant (where the prevailing winds in the region is western and southern Western). The results showed that the concentration of heavy elements in the bark of olive trees and lichens (ppm) take the same trend even thought there are differences in concentration between them by the overall average for all sites was as follows: iron > manganese > copper > lead. We note the high concentration of iron in bark of olive trees compared to lichens, but the rest of the elements it was statistically identical. The results also showed a significant correlation between the concentrations of manganese element in each of the bark and Lichens, and the existence of a negative correlation between the concentration of manganese and distance for both Lichens and bark. Concerning the altitude above sea level the results showed existence of significant and negative correlation with all of Iron, Manganese and Lead in Lichens.